Encyclopedia of postmodernism / edited by Victor E. Taylor and Charles E. Winquist - "Taylor, Victor E. (ed.) ; Winquist, Charles E. (ed.)" (London, 2001)
This book puts postmodernism in a specific social, historical and cultural context. Around this central concept, it defines the trace of evolution and development of the concept from different angles of view. This book collects more than 300 items relevant to the contemporary cultural phenomenon of ""postmodernism"". It is not only a necessary book for experts and scholars, but a convenient guide for ordinary readers to understand ""postmodernism.
Keywords: Postmodernism-encyclopedia